(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
This reflective and testimonial article aims to combine the author’s personal concerns and his academic research. The former arises primarily from his experience as facilitor of the Viewpoints practice at the Núcleo Experimental de Artes Cênicas do Sesi (Sesi Center for Performing Arts’ Experimental Nucleus) in São Paulo. The latter considers aesthetic issues from the 1960s and 1970s primarily in New York, as well as conceptual, philosophical, and practical issues in The Viewpoints Book: A Practical Guide to Viewpoints and Composition, by Anne Bogart and Tina Landau, and Standing in Space: The Six Viewpoints Theory & Practice, by Mary Overlie. In weaving together these reflections, the study leads us across the thoughts of authors such as Miriam Rinaldi, John Cage, and Sally Banes, among others.